Navigating The Workforce Challenges and Skill Development in The Era of Industry 4.0 - Bagas Ananta Aji; Disa Insanul Ikhlas; Intan Ratna Wati (LifeSciFi, 2023)
This study aims to explore the impact of employee competencies on organizational performance in the context of Industry 4.0, focusing on the essential skills required to adapt to technological advancements. With the rapid development of digital technologies and automation, employees are expected to possess a diverse set of competencies, including technical, digital, social, and personal skills. These competencies play a crucial role in addressing complex problems, fostering creativity, and ensuring organizational growth. A qualitative research approach is utilized, starting with a literature review to establish a theoretical framework on employee competencies, technological adaptation, and training practices. Data is collected through interviews with industry experts, HR managers, and employees to understand the specific challenges and opportunities related to workforce skill development. Data analysis is conducted using a descriptive approach, identifying recurring themes and trends in the competencies needed for Industry 4.0. The findings indicate that companies must prioritize continuous training and development programs to equip employees with the necessary skills to thrive in a rapidly evolving digital environment. The study highlights the importance of investing in employee competencies to drive organizational success, emphasizing the need for a proactive approach to skill development in an increasingly automated world